2007
DOI: 10.1007/s10840-006-9065-x
|View full text |Cite
|
Sign up to set email alerts
|

First-degree atrioventricular block

Abstract: Marked first-degree AV block (PR> or =0.30 s) can produce a clinical condition similar to that of the pacemaker syndrome. Clinical evaluation often requires a treadmill stress test because patients are more likely to become symptomatic with mild or moderate exercise when the PR interval cannot adapt appropriately. Uncontrolled studies have shown that many such symptomatic patients with normal left ventricular (LV) function improve with conventional dual chamber pacing (Class IIa indication). In contrast, marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…To solve this controversy, uncontrolled trials of pacing in marked first-degree AVB were carried out. The results showed that the patients' condition was improved with dual chamber pacing, specifically in patients with normal ejection fraction [18].…”
Section: Indications Of Pacing In Atrioventricular Blockmentioning
confidence: 93%
See 1 more Smart Citation
“…To solve this controversy, uncontrolled trials of pacing in marked first-degree AVB were carried out. The results showed that the patients' condition was improved with dual chamber pacing, specifically in patients with normal ejection fraction [18].…”
Section: Indications Of Pacing In Atrioventricular Blockmentioning
confidence: 93%
“…Some researchers suggest that pacing is only recommended for symptomatic patients; but others argue that pacing should be started earlier, regardless of symptoms, to improve survival especially for AVB that occurs diurnally [11]. Another study showed that marked first-degree AVB (PR ≥ 0.30s) can cause similar symptoms to the pacemaker syndrome without any existence of higher degree AVB [18]. To solve this controversy, uncontrolled trials of pacing in marked first-degree AVB were carried out.…”
Section: Indications Of Pacing In Atrioventricular Blockmentioning
confidence: 99%
“…Delayed atrioventricular conduction - 18,19 Occurs when the atrial impulses experience a delay or fail to reach the ventricles.…”
Section: Atrioventricular Conductionmentioning
confidence: 99%
“…The adverse hemodynamic effects may manifest clinically as a constellation of symptoms similar to pacemaker syndrome. Indeed, a pacemaker‐like syndrome is well recognized in patients with markedly prolonged PR interval, particularly if the prolonged PR interval fails to shorten on exercise 26 . Mabo et al demonstrated in a study of 17 patients with AAIR pacemaker, failure of the AV interval to shorten in six patients, and prolongation of the AV interval in five patients on exercise, resulting in symptoms of pacemaker syndrome in two patients 27 .…”
Section: Managed Ventricular Pacing™—adverse Effectsmentioning
confidence: 99%